2007
DOI: 10.5424/sjar/2007054-284
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Viability and pathogenicity of Ascosphaera apis preserved in integral rice cultures

Abstract: Chalkbrood is a fungal disease of honeybees (Apis mellifera L., Hymenoptera:Apidae) caused by Ascosphaera apis Maassen ex Claussen (Olive et Spiltoir). Ascosphaera apis is a heterothallic fungus that affects larvae of the honeybee. Diseased brood becomes mummified and mummies are white, gray, or black depending on the predominance of the sexual stage of the fungus. If spore-cysts are formed as a result of mating, infected larvae become gray or black in color. Larvae infected only by mycelia, without spore-cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In addition, A. apis isolates, as seen for many other microbes, can lose virulence when kept in culture with repeated transfers, thus it is important to utilize a long term storage method soon after an isolate is obtained. Two different culture preservation methods have been successfully used: cryopreservation (Jensen et al ., 2009a) and propagation on Integral Rice Kernels (IRK) (Palacio et al ., 2007). Contamination during storage seems to be less risky during cryopreservation at −80°C, however for larger quantities and for laboratories not equipped with cryopreservation capacity, the use of rice kernels is a great alterative.…”
Section: Chalkbroodmentioning
confidence: 99%
“…In addition, A. apis isolates, as seen for many other microbes, can lose virulence when kept in culture with repeated transfers, thus it is important to utilize a long term storage method soon after an isolate is obtained. Two different culture preservation methods have been successfully used: cryopreservation (Jensen et al ., 2009a) and propagation on Integral Rice Kernels (IRK) (Palacio et al ., 2007). Contamination during storage seems to be less risky during cryopreservation at −80°C, however for larger quantities and for laboratories not equipped with cryopreservation capacity, the use of rice kernels is a great alterative.…”
Section: Chalkbroodmentioning
confidence: 99%
“…These assays were performed with a concentration of 1,250 spores/hives. In this work, a concentration of 5x10 6 spores/mL was used and the percentage of mummies was lower than that found by Flores et al (2004) and Palacios et al (2007), when they used sugar syrup. Both authors warned that the percentage of mummification depends on the stress conditions of the larvae when they receive the ascospores or on their susceptibility to contract the ectoparasite according to the period of the year.…”
Section: Discussionmentioning
confidence: 71%
“…The pathogenicity also depends on the origin of the inoculum with ascospores. Flores et al (2004) performed the infection techniques with ascospores from macerated bee mummies, while Palacios et al (2007) maintained ascospores on integral rice kernels (IRK) medium and MY20. The lower percentages of infection of the larvae achieved by the direct method of feeding than those obtained in other works could be attributed to the ascospores coming from the cultivation of commercial pollen.…”
Section: Discussionmentioning
confidence: 99%
“…We found, as did Palacio et al (2007), that such spores were still infective to honey bee larvae. In our bioassays, 65% (SE = 0.1064) of the larvae exposed to the 500-spore dosages were killed by A. apis infections.…”
Section: Resultsmentioning
confidence: 80%
“…An alternative for A. apis is to store cultures on rice kernels (Ruffinengo et al, 2000). Palacio et al (2007) found viability to be 73% for A. apis stored in this way for one year. Thus, the viability over time was not as stable with this method as for the cryogenic storage used in our study.…”
Section: Resultsmentioning
confidence: 98%